Synthesis, structure and coordination chemistry of new mono- and bipodal N-acyl(aroyl)thiocarbamic-O-alkyl esters and N-acyl(aroyl)-N',N'-dialkylureas with Ni(II), Pd(II) and Cu(II) - Blewett, Gavin (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD) -- University of Stellenbosch, 2006.